If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x=-4x-2
We move all terms to the left:
x-(-4x-2)=0
We get rid of parentheses
x+4x+2=0
We add all the numbers together, and all the variables
5x+2=0
We move all terms containing x to the left, all other terms to the right
5x=-2
x=-2/5
x=-2/5
| 2(x+6)=3(x-8)-4x | | 8(5-4p)=4(-8p-6)-8p | | 3(7n+2)-7n=-4(-5n-8)-4n | | 2p+3=-13 | | -6x-5x=6(x+2)-2(6+3x) | | -7x+4x=-4(5+x)-(-4x+4) | | 420x+17=24+69x | | 4x×112=24×56 | | 6(4p-7)=6(p+2) | | 3(-2+7x)=2+2(1+8x) | | 6n-(n+8)=8(n+3)-5n | | x÷2-x+2÷7=2 | | 3(u−42)=90 | | -40=10-10s | | 108=5(-5n-7) | | -2k+3+7k=-8(k+8)+3(-1+6k) | | 5-10x=115 | | 4/3(x+3/5)=1.04 | | -30=12-6r | | -5(1+3v)=5(7+v) | | 3c−2c=1 | | -6(1-3x)=-3(5-7x) | | 5x-(3-4x)=1 | | (-9.8t^2)/2+32t=0 | | 8*x/8+7=22*8 | | 2x-8=-6x | | 8*x/8+7=22*7 | | 6(3n+5)=6(6n-7) | | 7(s+1)=84 | | -8(m+3)+6(m+7)=m-6-6 | | 5(t-82)=35 | | -(a-6)=-(7a-5)+5a |